2006
DOI: 10.1289/ehp.9466
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Perchlorate and Thyroid Hormone Levels in Adolescent and Adult Men and Women Living in the United States

Abstract: BackgroundPerchlorate is commonly found in the environment and known to inhibit thyroid function at high doses. Assessing the potential effect of low-level exposure to perchlorate on thyroid function is an area of ongoing research.ObjectivesWe evaluated the potential relationship between urinary levels of perchlorate and serum levels of thyroid stimulating hormone (TSH) and total thyroxine (T4) in 2,299 men and women, ≥ 12 years of age, participating in the National Health and Nutrition Examination Survey (NHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
237
8
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 294 publications
(250 citation statements)
references
References 51 publications
3
237
8
2
Order By: Relevance
“…In this analysis, we have estimated perchlorate intake distributions from the NHANES data in a manner similar to that employed by Blount et al (2006) in analyzing the 2001-2002 data. Differences in our approach include: (1) we have estimated distributions for reproductive-age women instead of for all adult females, and (2) we have used an updated approach to adjust for differences in 24-h creatinine excretion which takes into account racial differences in excretion rates (Mage et al, 2008).…”
Section: Perchlorate Intake Estimates Based On Nhanes Urinary Excretimentioning
confidence: 99%
See 1 more Smart Citation
“…In this analysis, we have estimated perchlorate intake distributions from the NHANES data in a manner similar to that employed by Blount et al (2006) in analyzing the 2001-2002 data. Differences in our approach include: (1) we have estimated distributions for reproductive-age women instead of for all adult females, and (2) we have used an updated approach to adjust for differences in 24-h creatinine excretion which takes into account racial differences in excretion rates (Mage et al, 2008).…”
Section: Perchlorate Intake Estimates Based On Nhanes Urinary Excretimentioning
confidence: 99%
“…Differences in our approach include: (1) we have estimated distributions for reproductive-age women instead of for all adult females, and (2) we have used an updated approach to adjust for differences in 24-h creatinine excretion which takes into account racial differences in excretion rates (Mage et al, 2008). In addition, we have generated two separate estimates of perchlorate intake, one based on the 2001-2002 data previously analyzed by Blount et al (2006) and another based on data from the 2003-2004 sampling rounds. In calculating these statistics, the NHANES survey weights were used; thus the derived distributions should correspond to the national distribution of perchlorate intake (within the limitations of the NHANES sampling scheme).…”
Section: Perchlorate Intake Estimates Based On Nhanes Urinary Excretimentioning
confidence: 99%
“…However, another recent study found that estimated perchlorate doses below the reference dose were associated with altered thyroid hormone levels in women with low iodine intake . One explanation of these different findings is that Tellez et al (2005) examined only three women with average urinary iodine o100 mg/l, while Blount et al (2006a) examined 348 women with urinary iodine o100 mg/l. Increased iodine intake could decrease the ability of a given dose of perchlorate to inhibit iodide transport.…”
Section: Introductionmentioning
confidence: 98%
“…In another study, Blount et al (2006) focused on urinary perchlorate and thyroid hormone levels in 2299 men and women participants who were 12 years of age and older from NHANES during [2001][2002]. The investigators evaluated the potential relationship between urinary levels of perchlorate and serum levels of thyroid stimulating hormone (TSH) and total thyroxine (T4).…”
Section: Introductionmentioning
confidence: 99%